A Spirituality of Reconciliation: Encouragement for Anglicans from a Roman Catholic Perspective - Sheldrake, Philip (Journal of Anglican studies, 2008)
The essay is a manifesto for keeping faith with the Christian vocation of reconciliation in the face of painful conflicts within the Anglican Communion. Its fundamental conviction is that, theologically speaking, reconciliation lies at the heart of Christian identity. The first part of the article concentrates on the key questions of the meaning and process of reconciliation, defined as ‘making space for what is other’, historically, psychologically and spiritually. The second part of the article focuses on the specifically Christian characteristics of reconciliation in terms of two theological themes, the catholicity of God (and its corollary the catholicity of the Church) and hospitality and in terms of spirituality related to insights from the Rule of St Benedict, Anglican sources and the practice of the Eucharist. The article concludes with brief reflections on the importance of applying wisdom from the Christian tradition of discernment to the current situation in the Communion.